2011
DOI: 10.2528/pierc11082801
|View full text |Cite
|
Sign up to set email alerts
|

A Circular Shaped Sierpinski Carpet Fractal Uwb Monopole Antenna With Band Rejection Capability

Abstract: Abstract-A novel planar ultra wideband (UWB) antenna using a second iteration Sierpinski carpet fractal shape with circular boundary is presented in this paper. The antenna covers the frequency band from 3 GHz to 12 GHz (VSWR ≤ 2). The proposed antenna has a meander shaped slot that renders the capability to reject 5.15-5.825 GHz band assigned for IEEE802.11a and HIPERLAN/2. The gain is suppressed very well in the desired WLAN bands. The measured antenna peak gain varies from 1.85 dBi to 6 dBi within the band.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…However this approach increases the circuit dimension. Hence to simplify the design and meet the band pass characteristics, slots can be cut in the patch and ground plane [5][6][7]. In this paper an elliptical shaped monopole Antenna with Triple band notch characteristics is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…However this approach increases the circuit dimension. Hence to simplify the design and meet the band pass characteristics, slots can be cut in the patch and ground plane [5][6][7]. In this paper an elliptical shaped monopole Antenna with Triple band notch characteristics is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…From Table 3 it is found that the geometry offers the maximum impedance bandwidth of 124%. Also, the defected ground behind the monopole geometries offer a wide impedance bandwidth [14][15][16][17], in this work we have included a finite ground of size equal to L g x W s . Width of the ground is chosen equal to the substrate width and length is chosen such that it covers only feed line of the monopole antenna.…”
Section: Effect Of Radius and Ground Dimensionsmentioning
confidence: 99%
“…With these exquisite structures, fractal is able to yield more ideal diversiform current distribution, so a fractal-shaped antenna generally has better radiation properties than Euclidean counterparts. Thus far, almost all fractal antennas comprise fractal geometries with straight segments or rectilinearly-edged blocks, such as Koch curve series [13][14][15], Minkowski curve [16], and Sierpinski Carpet series [8,[17][18][19][20]. Naturally, we conceive the idea of fabricating a fractal antenna with curved elements, such as circular or elliptical arc with hope of further enhancing performances -bandwidth, directivity, and gain.…”
Section: Introductionmentioning
confidence: 99%